Bioviability of Mangrove Leaves Extract (Sonneratia alba) on Fibroblast BHK-21 Cell Culture - Arlita Gladys Tricia Charyadie; Aprilia; Widyastuti (Denta Journal Kedokteran Gigi, 2017)
Background: Dental caries is a major oral health problem which is most commonly found in Indonesia. One of the main factors in role of causing dental caries is Streptococcus mutans which is the primary target of the prevention of caries. Leaf extract of Sonneratia alba has been proven to have an antimicrobial effect towards Streptococcus mutans, but its cytotoxic activity on normal cells is still unknown. The initial cell viability in this study was conducted using cell line BHK-21. Purpose: The aim of this study is to determine the cell viability of fibroblast cells line BHK-21 by given Sonneratia alba’s leaf extract. Materials and Methods: The experiment was conducted using post test only control group design. BHK-21 fibroblast cell culture on 96 wells were divided into cell control group (n=9), media control group (n=9) and test groups (n=9). The test groups were given various concentration of Sonneratia alba’s leaf extract, they were: 5%; 10%; and 20%. The cell cultures were incubated for 24 hours before and after treatment using Sonneratia alba’s leaf extract. After dripping MTT into the microplates, OD were read using ELISA reader and the viability were counted. The data that was acquired from the viability calculation was statistically analyzed using One Way ANOVA and LSD test. Results: Data showed the increase of viability cell in all the test groups. The highest viability cell showed by the test group with 10% concentration of Sonneratia alba (153,7122%±7,42458), and the lowest found in the test group with 20% concentration of leaf extract (141,4682%±7,48752). Conclusion: In this experiment, the leaf extract of Sonneratia alba proved to be nontoxic on fibroblast cells line BHK-21, the extract increased the viability and also caused proliferation of fibroblast cells.